Dynamic analysis and nonlinear simulation of aircraft flat spin. (18th August 2017) - Malik, Bilal; Akhtar, Suhail; Masud, Jehanzeb
Abstract: In this paper we investigate the dynamic characteristics of flat spin of a fighter aircraft in open-loop configuration. The aircraft model under study is of the multi-role fighter configuration co-sponsored by China and Pakistan. The aerodynamic model used in the study is in the form of look-up tables that have been developed from rotary balance steady coning and oscillatory coning motion wind tunnel data. The set of all possible equilibrium spin states is numerically computed for various values of control settings using eighth-order aircraft equations of motion. Results from dynamical systems theory are applied to investigate local stability characteristics of aircraft around steady spin state. The complete set of dynamic modes of aircraft in spin is evaluated and mode content in each of the motion variable is determined using modal decomposition. This analytical technique is complemented by performing numerical simulations to investigate flat spin dynamic features. The methodology is applied to investigate dynamic behavior of two flat spins: right flat spin at 72.1° and much flatter left spin at 84.4°. The presented work provides insight into the global overview of aircraft flat spins as a function of various control settings, and their dynamic characteristics and it can facilitate the designing of flight control laws for spin recovery/prevention.